Fostering Mutual Respect at Universiti Utara Malaysia: A Synergistic Approach Integrating Yusuf Al-Qardhawi's Moderation and Hamzah Fansuri's Sufi Thought - Muhamad Rizza; Lilis Sumarni; Siti Maryam (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2024)
This study explores the enhancement of interfaith communication and mutual respect at Universiti Utara Malaysia through the integration of Hamzah Fansuri's Sufi teachings and Yusuf Al-Qardhawi's principles of religious moderation. Utilizing a systematic literature review (SLR) methodology, the research investigates how Fansuri’s mystical Sufi doctrines—focused on compassion, spiritual unity, and personal transformation—can be effectively combined with Al-Qardhawi's moderation framework, which encourages amicable and respectful interactions across different faiths. The literature review critically examines existing scholarship on both Hamzah Fansuri’s and Al-Qardhawi’s ideologies, aiming to propose practical ways to align these theoretical perspectives with the university’s policies and instructional practices. The study synthesizes insights from these philosophical frameworks to suggest methods for integrating them into the campus environment, thereby fostering a more inclusive and respectful academic community. The findings indicate that incorporating Al-Qardhawi’s moderation principles with Sufi concepts of tolerance and empathy can significantly enhance campus harmony. Practical recommendations are offered for applying these integrated approaches, with the expectation that such measures will improve academic engagement, strengthen social cohesion, and cultivate a more respectful and understanding culture among students and faculty. Ultimately, the study aspires to contribute to a more harmonious and civil environment at Universiti Utara Malaysia